2006
DOI: 10.1080/01674820500260207
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of amniocentesis on women and their spouses: Importance of the testing period and genetic counseling

Abstract: The psychological impact of amniocentesis on women and their spouses does not constitute a major obstacle to their ability to cope. However, a certain number of couples reported feelings of uncertainty, tension and anxiety about fetal injury. We strongly suggest that counseling should be given to high-risk families and that prenatal/antenatal care units must be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…These findings extend previous evidence on the roles of social influences in reproductive choices by demonstrating the strong links of these two social influence factors on decisional conflict. During pregnancy, women tend to seek different providers for different types of support . For informational support (e.g., provision of facts), expectant parents usually consult medical professionals .…”
Section: Discussionmentioning
confidence: 99%
“…These findings extend previous evidence on the roles of social influences in reproductive choices by demonstrating the strong links of these two social influence factors on decisional conflict. During pregnancy, women tend to seek different providers for different types of support . For informational support (e.g., provision of facts), expectant parents usually consult medical professionals .…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study highlighted several themes related to the thoughts and feelings experienced by women undergoing amniocentesis, some of which refer to worry about the invasiveness of the procedure – both for maternal and fetal safety, anxiety while waiting for the results, and thoughts about a lifetime commitment in the case of a abnormal result . Amniocentesis is accompanied with elevated levels of anxiety in pregnant women both before the procedure and while waiting for the results, where the most prominently reported emotions were uncertainty and tension . Elevated levels of anxiety and stress during pregnancy are related to fetal activity and negative obstetrical outcome .…”
Section: Introductionmentioning
confidence: 99%
“…Decisions regarding screening and testing can be pivotal in a pregnancy and are often reported to be anxiety provoking, distressing, and emotionally charged . However, existing research suggests that women are not always fully informed about screening or testing prior to making a decision, and neither are their partners . In order to aid informed decision making, it has been found that women and their partners need to have accurate, balanced, and comprehensible information available to them and feel able to seek advice and ask questions where appropriate .…”
Section: Introductionmentioning
confidence: 99%